Coordination Behavior of 1,4-Disubstituted Cyclen Endowed with Phosphonate, Phosphonate Monoethylester, and H-Phosphinate Pendant Arms - Bárta, Jiří; Hermann, Petr; Kotek, Jan (Molecules, 2019)
Three 1,4,7,10-tetraazacyclododecane-based ligands disubstituted in 1,4-positions with phosphonic acid, phosphonate monoethyl-ester, and H-phosphinic acid pendant arms, 1,4-H4do2p, 1,4-H2do2pOEt, and 1,4-H2Bn2do2pH, were synthesized and their coordination to selected metal ions, Mg(II), Ca(II), Mn(II), Zn(II), Cu(II), Eu(III), Gd(III), and Tb(III), was investigated. The solid-state structure of the phosphonate ligand, 1,4-H4do2p, was determined by single-crystal X-ray diffraction. Protonation constants of the ligands and stability constants of their complexes were obtained by potentiometry, and their values are comparable to those of previously studied analogous 1,7-disubstitued cyclen derivatives. The Gd(III) complex of 1,4-H4do2p is ~1 order of magnitude more stable than the Gd(III) complex of the 1,7-analogue, probably due to the disubstituted ethylenediamine-like structural motif in 1,4-H4do2p enabling more efficient wrapping of the metal ion. Stability of Gd(III)-1,4-H2do2pOEt and Gd(III)-H2Bn2do2pH complexes is low and the constants cannot be determined due to precipitation of the metal hydroxide. Protonations of the Cu(II), Zn(II), and Gd(III) complexes probably takes place on the coordinated phosphonate groups. Complexes of Mn(II) and alkali-earth metal ions are significantly less stable and are not formed in acidic solutions. Potential presence of water molecule(s) in the coordination spheres of the Mn(II) and Ln(III) complexes was studied by variable-temperature NMR experiments. The Mn(II) complexes of the ligands are not hydrated. The Gd(III)-1,4-H4do2p complex undergoes hydration equilibrium between mono- and bis-hydrated species. Presence of two-species equilibrium was confirmed by UV-Vis spectroscopy of the Eu(III)-1,4-H4do2p complex and hydration states were also determined by luminescence measurements of the Eu(III)/Tb(III)-1,4-H4do2p complexes.
Keywords: Europium; Manganese; Phosphinic Acids; teplota; Potentiometry; Heterocyclic Compounds; komplexní sloučeniny; spektrofotometrie ultrafialová; europium; Contrast Media; heterocyklické sloučeniny; krystalografie rentgenová; Ligands; Coordination Complexes; Temperature; magnetická rezonanční spektroskopie; organofosfonáty; potenciometrie; kontrastní látky; Spectrophotometry, Ultraviolet; gadolinium; mangan; Magnetic Resonance Spectroscopy; Crystallography, X-Ray; kyseliny fosfinové; Organophosphonates; ligandy; Gadolinium